DESIGN AND IMPLEMENTATION OF LICENSING INFORMATION SYSTEMS IN THE OUTSIDE OF EMPLOYEES AT PT.SINTECH BERKAH ABADI - Azizah, Nur; Anisa, Nike Nur; Auzadina, Yosa (Pandawan, 2019)
Along with the development of current technology that has been very sophisticated and rapidly happening in this world, namely in a company, agency, even the world of education as well. At PT Sintech Berkah Abadi has an obligation to give permission to employees who submit. At this time, the management of employee exit permits is still running manually and has not been centralized computerized. Therefore, it requires papers in each process and is less efficient and it is difficult to control permit approval by employees if the HRD and the Chair are outside the office. The method used to develop an information system is to apply the analytical method using SWOT analysis, as well as data collection methods, there are three stages that must be done in collecting data, namely, Observation, Interview, and determining Literature Review (Literature Study) with the journal. The design method is done using the Unified Modeling Language (UML), Notepad ++, XAMPP and the web browser used to open the web that has been designed, Google Chrome. With the licensing system in and out of employees at PT Sintech Berkah Abadi can make it easier for employees to permit and more efficient in its use because they do not have to wait for HRD or leaders when outside the city.